Clinical Approach of Ankyloglossia in Babies: Report of Two Cases - Cunha, Robson Frederico [UNESP]; Silva, Janaina Zavitoski; Faria, Max Douglas (Journal Pedodontics Inc, 2008)
Ankyloglossia is a developmental anomaly of the tongue characterized by a short lingual frenum, resulting in restricted movement of the tongue. Its etiology is undefined and there is no gender preference. Few studies are available in the literature and the diagnosis and management of ankyloglossia in infants remains controversial. We report two cases of infants submitted to lingual frenectomy, emphasizing the management of ankyloglossia and its implications in breast-feeding.
Keywords: lingual frenectomy; babies; ankyloglossia